Wood energy in developed economies : resource management, economics and policy - Aguilar, Francisco X. (Abingdon, Oxon : Routledge, 2014)
'There has been a recent resurgence of interest in wood energy as part of a sustainable range of renewable energy options. This book addresses the current gap in the energy and public policy literature for a reference book that compiles the most-recent wood energy assessments, and evaluates current and potential future wood energy uses and the role for public policy to foster efficient use of the most-widely consumed renewable energy in the world. It brings together a group of expert authors covering topics from forest management, operations and engineering, to socio-economics and energy policy perspectives. It thus covers practical issues such as silviculture, harvesting, processing, comparative cost estimates, public policy tools and market effects. As such the book provides a comprehensive review of the complex dimensions of wood energy as well as practical guidance for professionals, researchers and advanced students. It will also provide invaluable guidance for economic development agencies, practitioners and policy-makers, when evaluating the impacts of wider wood energy adoption as part of a strategy for sustainable energy generation. The main focus is on industrialised production and developed economies, particularly the USA and Europe'--
Includes bibliographical references and index.
Keywords: Fuelwood industry -- Europe; Fuelwood industry -- North America; Fuelwood industry -- Government policy -- Europe; Fuelwood industry -- Government policy -- North America; Renewable energy sources -- Europe; Renewable energy sources -- North America